Beyond Point Masses. IV. Trans-Neptunian Object Altjira Is Likely a Hierarchical Triple Discovered through Non-Keplerian Motion - Maia A Nelsen; Darin Ragozzine; Benjamin C. N. Proudfoot; William G. Giforos; Will Grundy (The Planetary Science Journal)
Dynamically studying trans-Neptunian object (TNO) binaries allows us to measure masses and orbits. Most of the known objects appear to have only two components, except (47171) Lempo, which is the single known hierarchical triple system with three similar-mass components. Though hundreds of TNOs have been imaged with high-resolution telescopes, no other hierarchical triples (or trinaries) have been found among solar system small bodies, even though they are predicted in planetesimal formation models such as gravitational collapse after the streaming instability. By going beyond the point-mass assumption and modeling TNO orbits as non-Keplerian, we open a new window into the shapes and spins of the components, including the possible presence of unresolved “inner” binaries. Here we present evidence for a new hierarchical triple, (148780) Altjira (2001 UQ _18 ), based on non-Keplerian dynamical modeling of the two observed components. We incorporate two recent Hubble Space Telescope observations, leading to a 17 yr observational baseline. We present a new open-source Bayesian point-spread function fitting code called nPSF that provides precise relative astrometry and uncertainties for single images. Our non-Keplerian analysis measures a statistically significant (∼2.5 σ ) nonspherical shape for Altjira. The measured J _2 is best explained as an unresolved inner binary, and an example hierarchical triple model gives the best fit to the observed astrometry. Using an updated non-Keplerian ephemeris (which is significantly different from the Keplerian predictions), we show that the predicted mutual event season for Altjira has already begun, with several excellent opportunities for observations through ∼2030.